2012
DOI: 10.5267/j.msl.2011.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Work capacity assessment of Nigerian bricklayers

Abstract: The main aim of this study is to assess the physical work capacity of bricklayers with focus on the energy expenditure during work. Eighty Nine bricklayers' working on various sites in Ibadan and Eruwa towns of Oyo State, Nigeria are used for the study. Correlation and regression analysis using SPSS 16.0 Statistical Package was used to determine the relationship between VO2 given the age and weight of the subjects; % RHR(Relative Heart Rate) and working heart rate (HRW) given weight; VO2 and %RHR given Body Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The energy expenditure of workers was found to fall under the heavy workload category as recommended by the Indian Council of Medical Research (2010).The heart rate of workers also indicated that their job fell under the heavy workload category as it exceeded 120 beats/min which ultimately puts adverse stress on the human body (Maiti, R., 2008). The mean BMI of the majority of workers exceeded the normal range, and this consequently lowers the physical work capacity of these workers (Ismaila, S., Oriolowo, K., et al, 2012;Xu, X., Mirka, G. A. et al, 2008). The results from the Analytical Hierarchy Process showed the physical workload as the most significant factor as the workers lift and carry 50 kg loads for 7.5 meters.…”
Section: Discussionmentioning
confidence: 98%
“…The energy expenditure of workers was found to fall under the heavy workload category as recommended by the Indian Council of Medical Research (2010).The heart rate of workers also indicated that their job fell under the heavy workload category as it exceeded 120 beats/min which ultimately puts adverse stress on the human body (Maiti, R., 2008). The mean BMI of the majority of workers exceeded the normal range, and this consequently lowers the physical work capacity of these workers (Ismaila, S., Oriolowo, K., et al, 2012;Xu, X., Mirka, G. A. et al, 2008). The results from the Analytical Hierarchy Process showed the physical workload as the most significant factor as the workers lift and carry 50 kg loads for 7.5 meters.…”
Section: Discussionmentioning
confidence: 98%
“…The following data were obtained from the subjects after the purpose of study has been thoroughly explained to them and they all gave their consents; age in years, heart beat rate per minute at rest and while working, volume of oxygen consumption while working (VO 2w ). The heart beat rate per minute for each worker was measured as described by [13]. Measurement of heart beat rate per minute while at rest (HR r ) and when working (HR w ) were taken three times for each worker and the mean value for each were recorded as the heart beat rate per minute while at rest and while working respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As activities of ergonomists are becoming more in Nigeria, research works are being conducted in order to solve workplace problems that are associated with manual tasks; e.g. [12] and [13]. However the case of oil and gas industry in Nigeria seems not to have been explored sufficiently perhaps due to high level of automation in the sector.…”
Section: Introductionmentioning
confidence: 99%